E-Commerce, competition & ASEAN economic integration - Lee, Cassey; Lee, Eileen (Singapore : ISEAS-Yusof Ishak Institute, 2020)
The e-commerce market has grown rapidly within the ASEAN region in recent years. This trend is expected to continue in the future given the region's large population base, rising middle-class and improvements in connectivity. This edited volume examines the current state of e-commerce in ASEAN countries. It highlights some of the key domestic and cross-border challenges faced by ASEAN member states in developing e-commerce. These challenges include the regulatory and legal environment in which e-commerce firms operate across ASEAN, and the supporting infrastructure in ASEAN member states. "A comprehensive snapshot of the latest emerging regulatory, policy and consumer issues. It's essential reading for anyone working in this field. E-commerce is fundamentally altering the way in which businesses are being conducted, both within and between ASEAN countries. More than just an alternate distribution channel, online trading offers new opportunities and challenges for consumers, businesses, regulators and policymakers. How do markets operate in the new paradigm? How should regulators and governments ensure that dynamic competitive economies evolve, instead of descending into anti-competitive structures? And how are markets evolving in different parts of Southeast Asia? All of these issues - and much more - are discussed in here. The editors are to be congratulated for assembling a range of insightful perspectives from across ASEAN. These are issues that will affect the region for many years to come. The lessons here are timely and timeless." -Michael Schaper Ph.D., Deputy Chairman, Australian Competition and Consumer Commission, 2008-18
Title from publisher's bibliographic system (viewed on 27 Jan 2020).
Keywords: Electronic commerce -- Southeast Asia; Competition -- Southeast Asia; Southeast Asia -- Economic integration